In pursuit of a better broiler: a comparison of the inactivity, behavior, and enrichment use of fast- and slower growing broiler chickens - Lauren C. Dawson (Elsevier, 2021)
ABSTRACT: Selection for rapid growth has produced heavier, more efficient broiler chickens, but has also introduced health and welfare issues, which may cause or be caused by inactivity. Rapid growth may also limit the performance of motivated behaviors, whereas the provision of enrichment may increase these behaviors and general activity. This study aimed to evaluate the inactivity, behavior patterns, and enrichment use of 2 fast- (CONV) and 12 slower growing broiler strains (categorized as fastest [FAST], moderate [MOD], and slowest slow [SLOW]), based on their growth rates; 4 strains/category]. To evaluate inactivity, one male and one female from 153 pens were outfitted with omni-directional accelerometers from d 21 until processing (14–24 birds/strain from 8 to 12 pens/strain). Additionally, to supplement inactivity data, 5-min continuous behavioral observations of four focal birds per pen (2 males, 2 females) were conducted on days 26, 42, and 56 (72–148 observations of 8–12 pens/strain) to quantify the duration and frequency of various behaviors; at the same time, 5 to 11 instantaneous scan samples were also performed for pen-based enrichment use. Inactivity peaked at 78 to 80% of the day for all strains; however, those with slower growth rates reached these levels at older ages. Compared to slower growing strains at the same age, faster growing strains were more inactive, spent more time sitting and feeding, spent less time standing and walking, and used enrichments less; these differences mostly occurred at younger ages. Generally, at the same age, strains with similar growth rates (within the same category) behaved similarly, with only a few exceptions. Results suggest that not all strains identified as “slow-growing” broilers behave differently from fast-growing broilers, nor do they all behave similarly to each other. As such, results suggest that improved broiler welfare, particularly with respect to reduced inactivity, the performance of a wider range of normal, motivated behaviors, and/or increased enrichment use, is related to the broiler strain's specific growth rate.